Future drive : electric vehicles and sustainable transportation - Sperling, Daniel (Island Press, 1995)
In Future Drive, Daniel Sperling addresses the adverse energy and environmental consequences of increased travel, and analyzes initiatives and strategies for creating a more environmentally benign system of transportation. He discusses how to exploit the revolution in automotive technologies, why today's auto industry is fundamentally unprepared for the vehicles of tomorrow, why improving technology holds more promise than large-scale behavior modification, and why a.